Health-related quality of life after serious occupational injury in Egyptian workers: a cross-sectional study. Issue 6 (27th November 2012) - Salah Eldin, Waleed; Hirshon, Jon Mark; Smith, Gordon S; Kamal, Abdel-Aziz Mohamad; Abou-El-Fetouh, Aisha; El-Setouhy, Maged
Abstract : Objectives: Occupational injuries can have severe socioeconomic consequences; however, little research has examined the health-related quality of life (HRQoL) of workers following occupational injuries, especially in developing countries. This study was to employ the European Quality of Life Five Dimensions (EQ-5D) tool to measure HRQoL 6 months following serious occupational injury sustained by insured workers in the East Delta Region of Egypt. Design: This cross-sectional study was conducted from July to December 2008 among workers injured severely enough to be off work for at least 6 months after an occupational injury. Setting: The Nile Insurance Hospital in Qalyubia, Egypt. Participants: Adult workers returning for follow-up evaluation after being given 6 months off work by a physician for an occupational injury. Outcomes: The workers described their health and quality of life using the EQ-5D instrument. Results: Most study participants were male (n=118 (90%)), with mean age of 41.5 years. Fractures were the most common type of injury (n=96 (73%)), mostly involving the lower limbs (n=70 (53%)). Participants identified persistent problems related to mobility (n=78 (60%)), self-care (n=69 (53%)), performing usual activities (n=109 (83%)), pain/discomfort (n=119 (91%)) and anxiety/depression (n=51 (40%)). The perceived HRQoL estimated by the mean (±SD) visual analogue scale (VAS) score among injured workers was 61.6±17.9. Multivariate linear regression showed an association between poor VAS score and amputations, mobility limitation, self-care problems, pain/discomfort and anxiety/depression. Conclusions: Some people with occupational injuries experience significant problems such as pain/discomfort, functional limitations and anxiety/depression, long after the injury. Improvement in pain management strategies and physical and psychological rehabilitation may improve their health-related quality of life.